2009
DOI: 10.1007/s10029-009-0576-0
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results of inguinal hernia treatment with the Prolene Hernia System in a regional training hospital

Abstract: In a regional training hospital, the recurrence rate and long-term complications of patients treated for inguinal hernia with the PHS are acceptable after a follow-up of 5.5 years. The number of patients experiencing persistent pain seems to decrease over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The prevalence varies substantially depending on the definition used, the population under study and the method and timing of assessment. The literature shows that the prevalence of CPSP decreases over time after surgical procedures, such as hernia repair (Eklund et al, 2010;Faraj et al, 2010), breast augmentation (Kaasa et al, 2010), mastectomy (Macdonald et al, 2005) and thoracic surgery (Maguire et al, 2006). The literature shows that the prevalence of CPSP decreases over time after surgical procedures, such as hernia repair (Eklund et al, 2010;Faraj et al, 2010), breast augmentation (Kaasa et al, 2010), mastectomy (Macdonald et al, 2005) and thoracic surgery (Maguire et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence varies substantially depending on the definition used, the population under study and the method and timing of assessment. The literature shows that the prevalence of CPSP decreases over time after surgical procedures, such as hernia repair (Eklund et al, 2010;Faraj et al, 2010), breast augmentation (Kaasa et al, 2010), mastectomy (Macdonald et al, 2005) and thoracic surgery (Maguire et al, 2006). The literature shows that the prevalence of CPSP decreases over time after surgical procedures, such as hernia repair (Eklund et al, 2010;Faraj et al, 2010), breast augmentation (Kaasa et al, 2010), mastectomy (Macdonald et al, 2005) and thoracic surgery (Maguire et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the highest prevalence has been reported in retrospective studies, while prospective studies report lower prevalence (Lahtinen et al, 2006;Choini ere et al, 2014). The literature shows that the prevalence of CPSP decreases over time after surgical procedures, such as hernia repair (Eklund et al, 2010;Faraj et al, 2010), breast augmentation (Kaasa et al, 2010), mastectomy (Macdonald et al, 2005) and thoracic surgery (Maguire et al, 2006). Although the literature for cardiac surgery is limited, Choini ere et al (2014) have shown that post cardiac surgical pain continues to decrease during the first 2 years after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, underlay patch is quite suffi cient to overlay the entire region and all the weak points to prevent recurrence. In our series, we had only one (1.32%) recurrence, while other studies with PHS hernioplasty report recurrence rate from 0 to 2.3% 10,18,19 . In one patient with recurrent inguinal hernia after 'plug free' PHS hernioplasty, in reoperation we found enlargement of internal inguinal ring, which was not covered by onlay patch.…”
Section: Discussionmentioning
confidence: 42%
“…In 4801 repairs, they reported only "two patients with chronic neuralgia", accounting for 0.04% in their paper 9 . Later, other researchers found higher incidence of chronic neuralgia or chronic pain after PHS hernioplasty: 0.7%, 1.6%, 1.8% to up to 3.2% and even more in a smaller number of patients 3,[10][11][12] . 'Plug in' PHS hernioplasty is not the only procedure that results in chronic pain, since other plug and patch techniques also result in chronic pain in approximately 3% 13 .…”
Section: Discussionmentioning
confidence: 99%
“…4 Various studies in the past have evaluated the efficacy of PHS mesh for inguinal hernia. 6,[12][13][14] Present study shed light into the complications which had hindered the widespread usage of PHS. It may help in alleviating some of the apprehensions associated with PHS mesh repair.…”
mentioning
confidence: 99%